Cellular antioxidant and viability efficacy of Harpephyllum caffrum peel and Syzygium guineense seed extracts. (October 2022) - Pfukwa, Trust M.; Pheiffer, Wihan; Fawole, Olaniyi A.; Manley, Marena; Mapiye, Cletos
Abstract: Crude phenolic extracts of indigenous sub-Saharan fruit byproducts have potent antioxidant activity. Purification of these extracts and evaluation of their antioxidant activity and viability using appropriate biological models, has, however, not yet been completed. The current study quantitatively evaluated the phenolic composition and in vitro antioxidant activity of crude and purified extracts (PE) of Harpephyllum caffrum peel (HCP) and Syzygium guineense seed (SGS), and cellular antioxidant and viability efficacy of the PE. Phenols were extracted by 60% ethanol (v/v) solvent system and purified using XAD7HP macroporous adsorption resin. The UPLC/Q-TOF-MS was used for the characterization and identification of phenols. Cellular antioxidant activity (CAA) assay was applied to assess the antioxidant efficacy and cytotoxicity of the PE. Analysis of variance of data was done using a generalized linear mixed model with fruit type, extract purity and their interaction as fixed effects. Purification increased ( P ≤ 0.05) HCP total phenolic concentration (TPC) by over 200%, while SGS TPC decreased ( P ≤ 0.05) by 20%. Regardless of fruit type, PE had higher ( P ≤ 0.05) quantities of proanthocyanidins and anthocyanins than crude extracts. The HCP-PE had greater ( P ≤ 0.05) in vitro antioxidant activity than the other extracts ( P ≤ 0.05). Cellular antioxidant activity of HCP-PE was comparable to that of sodium metabisulphite ( P > 0.05). Also, HCP-PE had lower ( P ≤ 0.05) cytotoxic effects than SGS and sodium metabisulphite with increasing antioxidant concentration. It was concluded that HCP-PE is a potential source of safe natural antioxidants for nutraceutical applications. Graphical abstract: Image 1 Highlights: Phenolic composition of purified was higher compared to crude. Purified extracts had higher DPPH and FRAP antioxidant activity compared to crude ones. Cellular antioxidant activity (CAA) for purified extracts was higher in H. caffrum than S. guineense. The H. caffrum extracts had lower toxicity with increasing concentration.